Promosi Kesehatan Melalui Media Leaflet untuk Meningkatkan Pengetahuan dan Keterampilan Perawat tentang Universal Precaution HIV/AIDS di Rumah Sakit Umum Tere Margareth 2024 - Bestin Valentina Hulu; Ismail Efendi; Aida Fitria (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The implementation of Universal Precaution in hospitals is crucial to prevent the transmission of infectious diseases through blood and body fluids between patients and healthcare workers. This study aimed to evaluate the effectiveness of health promotion using leaflets in improving nurses' knowledge and skills regarding Universal Precaution for HIV/AIDS at Tere Margareth General Hospital Medan. The study employed a quasi-experimental design with a *Pre-Test and Post-Test with Non-Equivalent Control-Group Design* approach. The study population consisted of 36 nurses, all of whom were included as the sample using a saturated sampling technique. Data were analyzed using univariate, bivariate, and multivariate methods with a paired *t-test* at a 95% confidence level (P<0.05). The results showed that health promotion through leaflets significantly improved knowledge (sig. 0.004) and skills (sig. 0.000) of nurses regarding Universal Precaution for HIV/AIDS. It is recommended that nurses continue to enhance the implementation of Universal Precaution in hospital settings to optimize infection prevention. Education through leaflets can be an effective method to improve the understanding and skills of healthcare professionals.